PENINGKATAN PERFORMA JARINGAN DATA CENTER DENGAN SOFTWARE-DEFINED NETWORK (SDN) CISCO ACI (Studi Kasus : PT XYZ) - Sulistyo, Febryo Ponco (Universitas Mercu Buana, 2024)
The rapid growth of data-intensive applications and the increasing demand for real-time data processing have placed significant pressure on traditional data center architectures. To address the challenges of scalability, agility, and efficient resource utilization, Software-Defined Networking (SDN) has emerged as a transformative technology. One prominent SDN solution in the market is Cisco Application Centric Infrastructure (ACI), which offers a comprehensive and programmable approach to data center networking. This research aims to investigate the impact of utilizing SDN Cisco ACI in enhancing data center performance. The study focuses on exploring the key features and functionalities of SDN Cisco ACI, its ability to optimize network resource allocation, and its impact on improving data center performance metrics such as latency, bandwidth utilization, and scalability.